Role of Brand Image and Price Importance as Moderator on Online Customer Review and Hotel Booking Intention - Rania Salsabila; Citra Kusuma Dewi; Putu Nina Madiawati (Binus Business Review, 2025)
The increasing ease of Internet access has led to the widespread use of Online Travel Agents (OTAs), especially in the tourism industry. OTAs simplify hotel booking and increase consumer interest. A key factor influencing hotel booking intention is Online Customer Reviews (OCRs), which can be positive or negative and provide essential information to potential buyers. Despite the critical role of OCRs, limited research has been conducted on how brand image and price importance moderate the effect of reviews on hotel booking intentions, particularly in Indonesia. The research aimed to examine the impact of OCRs on hotel booking intention, with a focus on brand image and price importance as moderating factors on Indonesia’s largest OTA platform, Traveloka. Data were collected from 500 valid respondents and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to assess the influence of reviews, brand image, and price importance on booking intentions. The results demonstrate that positive OCRs significantly enhance booking intentions. Additionally, brand image and price importance play a crucial moderating role in strengthening the influence of reviews on consumer decisions. These findings highlight hotel managers’ importance in maintaining a positive online presence and leveraging their brand image and pricing strategies to maximize booking intentions. The research contributes to the theoretical understanding of OTA-mediated consumer behavior and offers practical insights for optimizing digital marketing strategies within the Indonesian tourism sector.